Households Willingness to Pay for the Emissions Reduction Policy, Queensland, Australia. (8th September 2015) - Williams, Galina
This study examines households' willingness to support the emissions reduction policy and their perceptions of climate change using an Internet survey of more than 1, 000 households in Queensland, Australia. Respondents were asked for their willingness to pay (WTP) to support the emissions reduction target proposed by the Australian Government by paying extra on their electricity bills. The results can be summarized in four key findings. First, respondents' WTP to support the emissions reduction target is higher if they perceive that climate change will result in high loss of biodiversity. Second, respondents were willing to support a higher emissions target than proposed by the Australian Government. Third, there is a correlation between respondents WTP to support the emissions reduction and their beliefs about climate change, its effect on standards of living, the environment, and future generations. Fourth, as the data show a high rate of zero responses, common for the contingent valuation method (CVM) used in the survey, the zero bids were further investigated using the non-parametric Turnbull model and the more recent spike model. The results showed that although there is some support for the emissions reduction policy, it is not sufficient for the policy to be successful.